Advances in using sewage sludge to remediate sulfidic mine tailings : An overview from pilot- and field-scale experiments, northern Sweden - Nason, Peter (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2013)
Sewage sludge can and has been used effectively as an organic-rich cover for sulfidic mine waste remediation. However, the optimum use of the material as a layer in engineered covers remains unconfirmed. Results obtained from four different sewage sludge applications are presented and discussed in context to their success and for their applicability for being used at full-scale sulfidic-mine waste remediation projects. The experiments evaluated sewage sludge when used as a vegetation substrate on bare tailings, a water-saturated cover, a composite cover, and lastly when used as a sealing-layer barrier material, which was deemed the most successful technique. Godkänd; 2013; 20130916 (petnas)